A Critique and Review on Psychology of Language - Shima Nabifar (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This article aims to investigate Psychology of Language, written by David W Carroll, translated by Heshmatollah Sabaghi.  The book is described considering the form and the content. Then, the translation of  the book is assessed  based on factors such as the style of writer, Persian equivalents of general and psycholinguistics terms, grammatical structures, punctuations, writing rules and conventions, accuracy and faithfulness. The main problems of the translation were related to the spaces and half-spaces between the word and within compound words, the correct punctuation and the complexity of Persian sentences in translation in spite of the simplicity of their original English sentences, complex and less frequent equivalents and Arabic words instead of simple, frequent and familiar Farsi equivalents. The faithfulness principle in the translation was acceptable. The result of this study showed that although the translation of the book is acceptable, it is not of high quality. The most critical problem of the translation is the complexity of  Persian sentences, so that the readers have to read the sentences several times to understand them. However, considering the fact that there are few Persian sourcebooks written on psycholinguistics, it can be used as a sourcebook provided that the problems are eliminated in the next editions.